Integration of English ‘teaching-learning-assessing’ in Chinese High Schools: A Literature Review - Ting, Ye (International Journal of Humanities and Education Development (IJHED), 2023)
Classroom assessment has always been the focus of research on foreign language teaching, and "integration of teaching and assessment" has become a heated topic in international second language teaching field, but this topic has not yet attracted the attention of some scholars. In result, this paper retrieves the papers published domestic and abroad between 2017 and 2023 focusing on the "integration of teaching and evaluation" in English subject as data sources and analyzes the research contents. The results show that the research type of "integration of teaching-learning-assessing" is mainly theoretical research, but the number of empirical research is quite small. Besides, the theoretical research also shows an upward trend. The research objects are mainly secondary school English teachers and students. The research content focuses on the following four aspects: the definition of "integration of teaching-learning-assessing"; the implementation path of "integration of teaching-learning-assessing" in the classroom; the application of "integration of teaching-learning-assessing" in specific subjects and the investigation of "integration of teaching-learning-assessing" in the classroom. The data collection methods were mainly questionnaires, interviews and classroom observations. In the end of this paper, the future research and the development trend of "integration of teaching-learning-assessing" are pointed out.